2017
DOI: 10.3389/fnins.2017.00525
|View full text |Cite
|
Sign up to set email alerts
|

Unique Neural Characteristics of Atypical Lateralization of Language in Healthy Individuals

Abstract: Using functional magnetic resonance imaging (fMRI) in 63 healthy participants, including left-handed and ambidextrous individuals, we tested how atypical lateralization of language—i. e., bilateral or right hemispheric language representation—differs from the typical left-hemisphere dominance. Although regardless of their handedness, all 11 participants from the atypical group engaged classical language centers, i.e., Broca's and Wernicke's areas, the right-hemisphere components of the default mode network (DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 142 publications
0
18
0
Order By: Relevance
“…Studies have also often investigated the effect of handedness, with the same hypothesis that left-handers would have reduced brain lateralization and would be more prone to Left–Right Confusion ( Brandt and Mackavey, 1981 ). However, several studies that included a large sample of left-handers did not show any difference in hemispheric lateralization related to handedness ( Mazoyer et al, 2014 ; Tzourio-Mazoyer et al, 2015 ; Mellet et al, 2016 ; Biduła et al, 2017 ). In the same way, recent neuroimaging studies ( Hirnstein et al, 2011 ; Hjelmervik et al, 2015 ) found no reason to believe that sex differences in LRD were related to a more bilateral brain in women.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have also often investigated the effect of handedness, with the same hypothesis that left-handers would have reduced brain lateralization and would be more prone to Left–Right Confusion ( Brandt and Mackavey, 1981 ). However, several studies that included a large sample of left-handers did not show any difference in hemispheric lateralization related to handedness ( Mazoyer et al, 2014 ; Tzourio-Mazoyer et al, 2015 ; Mellet et al, 2016 ; Biduła et al, 2017 ). In the same way, recent neuroimaging studies ( Hirnstein et al, 2011 ; Hjelmervik et al, 2015 ) found no reason to believe that sex differences in LRD were related to a more bilateral brain in women.…”
Section: Discussionmentioning
confidence: 90%
“…It seems that using Eduball in the classroom would also require a miniaturization of these educational balls. We are currently developing a prototype of this type of mini-Eduball (the size of a tennis ball), which, by integrating cognitive activity with fine motor tasks, can offer even greater benefits than “big” Eduballs, as neural correlates of fine motor skills are much more closely related to language or numeracy neural circuits, compared to neural underpinnings of gross motor abilities ( Bidula et al, 2017 ; Klichowski and Kroliczak, 2017 , 2020 ; Przybylski and Kroliczak, 2017 ; Styrkowiec et al, 2019 ; Klichowski et al, 2020 ; Kroliczak et al, 2020 ; for the most recent evidences, see Kroliczak et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current investigation, we examined the reliability and validity of using threshold-independent LIs with three welldescribed fMRI localizers. For assessing lateralization of language, we adopted a subvocal verbal fluency measure that has been validated against the Wada technique in epileptic patients (Abbott et al, 2010) and has been frequently used in the growing fMRI asymmetry literature (Biduła, Przybylski, Pawlak, & Króliczak, 2017;Häberling, Steinemann, & Corballis, 2016;Hunter & Brysbaert, 2008;Powell, Kemp, & García-Finaña, 2012). For faces and bodies, we took advantage of a locally-available visual perception localizer, where visual stimuli are processed in a one-back task (Downing, Wiggett, & Peelen, 2007;Peelen, Wiggett, & Downing, 2006).…”
Section: Take Down Policymentioning
confidence: 99%